PENGARUH PROSES HARDENING PADA HASIL PENGELASAN DENGAN VARIASI MEDIA PENDINGIN OLI GARDAN, SERBUK ARANG, DAN AIR TEMPERATUR RENDAH - Pujiono, Akhmad; Feriansah, Arif; Rahman, Fadhillah (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2020)
Welding is a metal joining method that utilizes the penetration of heat or heat produced. Heat and then the cooling of the metal joints is a natural phenomenom. The cooling temperature is so fast that is creates a variety of structures so that the mechanicalability of a metal changes. This study aims to determine the effect of hardening with different cooling media on the result of SMAW welding. The test of the highest tensile strength value in the hardening proses with axe oil cooling media was 467.51N/mm2 and the lowest tensile strength value in the hardening process with charcoal powder cooling media was 427.40N/mm2. The highest hardening value test was in the hardening process using low temperature water cooling media of 202.62HB and the lowest hardening value in the hardening process using charcoal powder cooling media was 149.92HB.Key Word: SMAW welding, Hardening, Axle oil, Charcoal powder, Low temperature water